Holy Spirit and Missio Ecclesiae in Africa: Contexts, Diversity, and Confusion - Jiofack Kana C. Jésus (Conspectus)
Due to some points of connection between pneumatology and the African worldview, all sorts of paranormal experiences have been attributed to the Holy Spirit. This phenomenon has caused a section of the Church to view any emphasis on the Holy Spirit with suspicion. Interestingly, in theological research, discussions on pneumatology seem to be restrained to the reinforcement of orthodoxy, with little or no awareness of Africans’ spiritual concerns. The main thrust that drives this study is that a contextual approach to pneumatology can provide a beneficial tool for engaging African Christians in relevant reflections on the beliefs related to the spirit world and so provide Bible-based responses that will strengthen the witnessing of the church. This article uses a comparative approach to analyze some major representations of the Holy Spirit in the African Church movement that make the contextualization of pneumatology necessary. The research findings indicate that Western Systematic Theology does not make a definite statement about how non-Western Christians are to understand the works of the Holy Spirit in relation to the spirit world. While local pneumatologies do engage the African worldview, they often incorporate unbiblical categories and practices. This study proposes a hermeneutics of the Spirit and a praxis-based theology as two essential components of a contextual pneumatology for the Evangelical Church. Tis article is a contribution to reflections on a contextual theology of mission in Africa.